CONVERGENCE OF AGRO-BUSINESS STRUCTURES IN THE NEW MODEL OF GLOBALIZATION ECONOMY (INNOVATIVE ECONOMY, 2021)
Zinchuk T.O., Levkivskyі Ye.V. CONVERGENCE OF AGRO-BUSINESS STRUCTURES IN THE NEW MODEL OF GLOBALIZATION ECONOMYPurpose. The aim of the article is analysis and substantiation of possibilities of adaptation of agro-business structures to effective integration, intertwining of economic activity, convergence and unification (convergence) of their potentials that will promote overcoming of social and economic negative consequences of functioning of vertically integrated structures of holding type and strengthening of advantages of various organizational forms of enterprises small and medium agrarian business.Methodology of research. The methodological and theoretical basis of the study is theories and views presented in the works of foreign and domestic scientists. The results of the study are obtained using both general and special (economic) methods of scientific knowledge. The general historical context of convergence is considered on the basis of the historical and dialectical method; the method of analysis and synthesis is used in identifying global problems against the background of the economic crisis.Argumentation of theoretical provisions that characterize the patterns of convergence and the relationship of organizational forms of management in the agricultural sector, formed on a systematic analysis, the laws of logic, the method of scientific abstraction. Statistical, tabular and graphical methods are used for comparative analysis of economic performance of agricultural enterprises.Findings. The advantages and disadvantages of the existing agro-business structures in the conditions of new requirements of globalization, anticipated consequences of the economic crisis and orientation on the goals of sustainable development, on the basis of which objective conditions for the convergence process are formed, are revealed.Originality. It is substantiated that under the condition of convergence of different categories of enterprises the minimization of social and economic differences between them is ensured and inequalities in entering the domestic and foreign markets are levelled. Contrary to the existing radical views on the exceptional damage from the activities of agricultural holdings, a methodological approach is proposed, according to which transformational changes based on convergence will anticipate and minimize risks, especially in small and medium agribusiness, which will occur during pandemics and economic crisis. This approach will promote the cohesion of forms of management in the agricultural business, which reflects the experience of best management practices of developed countries.Practical value. The proposed scientific ideas and views on convergence, as a process of convergence and integration of potentials and resources of existing forms of management, can be used at the enterprise level, which will ensure a synergistic effect of their scale and compliance with sustainable development goals in a favourable institutional environment.Key words: agrarian business, agro-holdings, globalization, innovations, convergence, sustainable development, forms of management of agrarian enterprises.
Keywords: Key words; agrarian business; agro-holdings; globalization; innovations; convergence; sustainable development; forms of management of agrarian enterprises.